Evidence in Civil Law - Finland - Koulu, Riikka (Law & Society, 2015)
Finnish civil procedure has a close connection with other Scandinavian legal systems and co-operation between the States is active. In addition, the legislation, case-law and scholarly doctrine are more and more influenced by European co-operation through the EU and Council of Europe. The principles of free disposition, free assessment of evidence, audiatur altera pars, and burden of proof form the basis for an oral and direct public hearing. It follows from these due process principles that no methods of proof are forbidden but their relevance depends on the court's assessment. The procedural doctrine in Finland is well established and has roots in the Swedish code of civil procedure of 1734, although it has gone through extensive reforms. On February 10, 2015 the Parliament of Finland passed the reform of chapter 17 of code of civil procedure, which contains the legislation on law of evidence. The extensive reform systematically updates and streamlines the previous legislation on evidence in addition to introducing new regulation e.g. on anonymous witnesses and banning invocation of evidence, which has been obtained by illegal means. The reform of chapter 17 concludes the systematic reform.